Absence of Plekhg5 Results in Myelin Infoldings Corresponding to an Impaired Schwann Cell Autophagy, and a Reduced T-Cell Infiltration Into Peripheral Nerves - Lüningschrör, Patrick; Slotta, Carsten; Heimann, Peter; Briese, Michael; Weikert, Ulrich M.; Massih, Bita; Appenzeller, Silke; Sendtner, Michael; Kaltschmidt, Christian; Kaltschmidt, Barbara (Frontiers in Cellular Neuroscience, 2020)
Inflammation and dysregulation of the immune system are hallmarks of several neurodegenerative diseases. An activated immune response is considered as the cause of myelin breakdown in demyelinating disorders. In the peripheral nervous system, myelin can be degraded in an autophagy-dependent manner directly by Schwann cells or by macrophages, which are modulated by T-lymphocytes. Here, we show that the NF-κB activator Pleckstrin homology containing family member 5 (Plekhg5) regulates both, Schwann cell autophagy and recruitment of T-lymphocytes in peripheral nerves during motoneuron disease. Plekhg5-deficient mice show defective axon/Schwann cell units characterized by myelin infoldings in peripheral nerves. Even at late stages, Plekhg5-deficient mice do not show any signs for demyelination and inflammation. Using RNAseq we unraveled a transcriptional signature for an impaired immune response in sciatic nerves, which manifested in a reduced number of CD4+ and CD8+ T-cells. These findings identify Plekhg5 as a promising target to impede myelin breakdown in demyelinating PNS disorders.